Mechanical performance of cementless total knee replacements: It is not all about the maximum loads. Issue 2 (3rd January 2019) - Quevedo González, Fernando J.; Lipman, Joseph D.; Lo, Darrick; De Martino, Ivan; Sculco, Peter K.; Sculco, Thomas P.; Catani, Fabio; Wright, Timothy M.
ABSTRACT: Finite element (FE) models are frequently used to assess mechanical interactions between orthopedic implants and surrounding bone. However, FE studies are often limited by the small number of bones that are modeled; the use of normal bones that do not reflect the altered bone density distributions that result from osteoarthritis (OA); and the application of simplified load cases usually based on peak forces and without consideration of tibiofemoral kinematics. To overcome these limitations, we undertook an integrated approach to determine the most critical scenario for the interaction between an uncemented tibial component and surrounding proximal tibial bone. A cementless component, based on a modern design, was virtually implanted using computed‐tomography scans from 13 patients with knee OA. FE simulations were performed across a demanding activity, stair ascent, by combining in vivo experimental forces from the literature with tibiofemoral kinematics measured from patients who had received the same design of knee component. The worst conditions for the bone–implant interaction, in terms of micromotion and percentage of interfacial bone mass at risk of failure, did not arise from the maximum applied loads. We also found large variability among bones and tibiofemoral kinematics sets. Our results suggest that future FE studies should not focus solely on peak loads as this approach does not consistently correlate to worst‐case scenarios. Moreover, multiple load cases and multiple bones should be considered to best reflect variations in tibiofemoral kinematics, anatomy, and tissue properties. © 2018 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 37:350–357, 2019.